A Critical Examination of the Factors Leading to Organizational Silence and its Influence on Employee Job Attitudes - Ullah, Naqeeb; Asghar, Umair (2023)
To successfully and efficiently attain the purpose, personnel are seen as sources of development, innovation, learning, and progression. Nevertheless, a significant proportion of individuals choose quiet, refraining from expressing their beneficial emotions and concerns over the troubles inside their relationships. This research aims to use existing literature to ascertain the underlying motivations for employee silence and identify the many components that contribute to silence within an organizational context. The primary factors contributing to calmness are often acknowledged as workplace culture, fear and harsh criticism from the administration, lack of trust, and insufficient assistance from management. According to existing research, silence is a behavioral phenomenon that is linked to several work attitudes, including contentment, turnover intention, and organizational citizenship behavior. Workers are more inclined to express their concerns on corporate matters when a company fosters a climate of trust and has effective communication channels.